Mainstreaming equality at the Scottish Executive: the discursive construction of policy - Bilton, Katherine (The University of Edinburgh, 2005)
This thesis addresses the central paradox of gender and equality mainstreaming: namely that the remarkable diffusion of the strategy and its widespread adoption has been in stark contrast to the lack of evidence for any significant change in either governmental practice or concrete outputs. Despite high levels of political will mainstreaming appears to elude implementation.

The opportunities afforded by constitutional change in the UK to embed new norms and values in institutional design have been well exploited. Feminists have organised to ensure that the principle of equal opportunity was inextricably linked to the enhancement of democracy, and that a new Parliament would have a more equal balance of female and male representatives. Suggestions that Scotland provides a positive environment for the development of mainstreaming, however, have neglected the importance of the Civil Service as a force of continuity. This thesis addresses this gap.

A key aim of the thesis is to provide insight into the possibilities of inserting gender into an organisation designed with man in mind by exploring what it means to ask bureaucrats to work within a new frame. It locates this question in a study of the day-to-day interaction of policy makers directly involved in mainstreaming

The importance of framing by feminist advocates in securing the adoption of mainstreaming has been established elsewhere. The thesis examines the consequent potential for frame conflict between the norms and values of feminism and bureaucracy, and its implications for policy implementation. A key finding of the thesis is how frame conflict has been managed, or deferred, through a continual process of re-framing which is ultimately detrimental to policy implementation. Identifying and illuminating the underlying epistemological conflict between feminist and bureaucratic frames takes us beyond a simplistic understanding of patriarchal resistance as an explanatory factor for the lack of further progress in mainstreaming. It demonstrates that mainstreaming is fundamentally challenging to civil service ways of working and knowing, going to the heart of the way people operate in, and make sense of, their world. In so doing it furthers our understanding of the fundamental paradox presented by mainstreaming identified above.

The thesis contends that the current dominant emphasis in feminist policy analysis on framing as strategic action is limited with respect to the insights it offers into the complex processes of implementation. Instead it is argued that there is a need to return to earlier constructions of framing as shaping, organising and constructing how we 'know' about the world. This 'frame' of framing takes forward our understandings of the institutional dynamics that frustrate the implementation of transformatory feminist policy. As a policy study of mainstreaming, the thesis, in turn, contributes to the wider policy literature through its analysis of the dynamics of, and problems presented by, processes of implementation.